Purchase Price Mechanisms - Gajdošech, Martin (2013)
My diploma thesis focuses on the M&A transaction closing mechanisms. Their function is to reflect the value changes of the target company into the purchase price. Value change occurs during the time lag between the date of the financial statements and the date of the transaction closing. Throughout history, there have been two major approaches developed. The "Completion Accounts Mechanism" uses post-completion price adjustments to reflect the change of the net working capital and net debt during the interim period. The "Locked Box Mechanism", using fixed price, assures non-fluctuation of target value in the interim period by imposing strict restrictions on the seller's activities. In this research, I have analyzed 44 transactions closed in the Czech Republic. I have challenged the theoretical foundations and described the application of the mechanisms in practice. At the end, I have compared the Czech and European practices. Thesis findings: 1. All the theoretical features of the mechanisms were proven by an analyzed sample of closed transactions. The completion accounts mechanism is buyer-friendly, while the locked box is a seller-friendly mechanism. 2. The main driver in mechanism selection is bargaining power. Buyers were in a better negotiating position in 69% of the completion account transactions. On the contrary, the sellers had bargaining power in 100% of the locked box transactions. 3. The Czech Republic is an environment where buyers (big multinational companies) dominate. They have preferred the completion account mechanism that provides them with higher protection from value leakage or other risks associated with small CEE economies. A total of 91% of analyzed transactions were executed by the completion account mechanism in the Czech Republic between 2011 and 2012.